Perspektif Hukum Administrasi Negara dalam Konteks Pemusnahan Arsip di Komisi Pemilihan Umum - Sri Dwi Puji Lestari; Mohammad Abil Faroj Al Jawawi; Nur Azizah; Akiko Brando Yuniardi; Ahmad Heru Romadhon (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
The management and destruction of archives in state institutions is an important part of state administration that supports accountability and legitimacy in democratic governance. This research is motivated by a legal controversy regarding the destruction of registration archives for regional head candidates at the General Election Commission (KPU) of Surakarta, which was carried out without a Destruction Report and did not comply with the national archival retention schedule. The purpose of this research is to analyze the validity of the destruction of KPU archives in the context of Administrative Law and to identify the legal implications of deviations from archival procedures and substance. The research method used is normative legal research with a regulatory approach. The analysis is based on Law No. 43 of 2009 on Archives, Law No. 7 of 2017 on General Elections, PKPU No. 17 of 2023, and guidelines for Administrative Law. The results of the study show that the lawful destruction of KPU archives must meet material and formal requirements, such as compliance with the Archival Retention Schedule, inventorying of archives, written approval from ANRI, and the creation of a Destruction Report. Destruction of archives that does not meet these provisions can be annulled and weaken the accountability of the KPU.